Risk Assessment of Toxic Elements in Buckwheat Produced in Armenia - Pipoyan, Davit; Arshakyan, Yepraqsya; Beglaryan, Meline (ՀԱԱՀ հիմնադրամ)
Buckwheat provides essential nutrients crucial for the human body’s regular functioning, however, studies have indicated that it may also contain potentially toxic elements. Therefore, this study aims to assess the health risks associated with buckwheat produced in Armenia, focusing on dietary exposure to toxic elements (lead, cadmium, and arsenic). Risk assessment was conducted using the margin of exposure (MOE) method, involving calculating daily intakes for toxic elements. The study findings suggest that the levels of toxic elements in the investigated buckwheat samples were within acceptable limits. This indicates that there is no significant health risk to consumers.
Keywords: Food Science and Technology